Imagining the future of prison administration in response to the climate emergency - Julien Sipra; Anouk Mousset (Field Actions Science Reports)
Prison authorities around the world are already confronting the direct and indirect consequences of climate change. Heatwaves, coastal and inland floods, storms, droughts and swelling-shrinking of clay soils are the main climate hazards identified as posing risks to French prisons. After a brief overview of the possible impacts of climate change on prisons, this article presents actions taken by the prison administration’s laboratory to co-create a much-needed strategy for transformation that seeks to adapt to climate change as well as mitigate its impacts. The strategy, created by examining future environmental trends, aims to anticipate and suggest actions for different timescales: acquiring data and producing knowledge; visualizing what future prisons might look like and possible trajectories for their transformation; organizing collective discussions about prisons to establish a shared vision, and supporting appropriation of the results to assist in decision-making and action-taking.